Bringing Mindfulness into First-Year Composition - Matt Lemas (Journal of the Assembly for Expanded Perspectives on Learning, 2025)
I first stumbled upon the relationship between mindfulness and writing sometime after college. I had been meditating for a few years—not perfectly, but enough to notice the way it softened the inner critic and procrastinator that usually accompanied me to the page.